Global quantitative synthesis of effects of biotic and abiotic factors on stemflow production in woody ecosystems. Issue 8 (21st May 2021) - Zhang, Yafeng; Wang, Xinping; Pan, Yanxia; Hu, Rui; Chen, Ning
Abstract: Aim: Stemflow has been increasingly recognized as an indispensable component in water and nutrient budgets within vegetated ecosystems. Here we aim to quantify the stemflow percentage (St, %) of incident precipitation (i.e. stemflow production) at a global scale, and to provide a systematic evaluation on how biotic and abiotic factors affect St. Location: Global. Time period: 1970–2019. Major taxa studied: Woody plants (trees and shrubs). Methods: We compiled a global stemflow dataset from 234 peer‐reviewed papers, which included 488 observations of St and the related biotic (stand characteristics) and abiotic factors (climate variables) at 283 sites within terrestrial woody plant ecosystems. We explored the global pattern of St and performed a machine learning method (boosted regression trees) to model the effects of biotic and abiotic variables on St. Results: Globally, the median (interquartile range, IQR) St was 2.7% (1.0–6.3%). We found that St in arid zones (type B in the Köppen‐Geiger climate classification) was significantly higher ( p < .01) than in other climate types, and we also detected a significant difference ( p < .01) in St between trees (median: 2.4%; IQR: 1.0–5.3%) and shrubs (median: 7.2%; IQR: 5.2–11.9%). Predictor variables that substantially accounted for the explained deviance of the final model included vegetation height (27.0%), mean annual precipitation (16.1%), mean annual temperature (14.4%), stand density (10.8%), stand age (8.9%) and bark type (5.5%). In contrast, leaf area index, diameter at breast height, basal area, phenology type, life‐form and leaf type were classified as low importance. Main conclusions: Our synthesis provides a cross‐site comparison of St, and gives a holistic view on how climate variables and stand characteristics contribute to and affect global stemflow production.